PENGENDALIAN PERSEDIAAN BAHAN BAKU TEPUNG TERIGU DAN GULA PADA CV “dR anNur” BEKASI - Maulidya Ergy, Belinda Rizky; Danapriatna, Nana; Rahmanto, M. Ikhwan (CEFARS : JURNAL AGRIBISNIS DAN PENGEMBANGAN WILAYAH, 2024)
CV “dR. anNur” Bekasi is a manufacturing company that primarily utilizes wheat flour and granulated sugar as raw materials. The company faces significant challenges in inventory management due to a simplistic approach that results in discrepancies between actual and required inventory levels. This inefficiency leads to increased inventory holding costs and reduced operational profitability. The aim of this study is to develop a more effective and efficient inventory control system to minimize inventory-related costs and enhance overall company performance. This research employs a quantitative descriptive method, utilizing data collection techniques such as observation, interviews, and documentation. The analysis is conducted using the Economic Order Quantity (EOQ) model as the proposed inventory control method. The findings indicate that implementing the EOQ model provides significant efficiency improvements compared to the company’s current practices. Specifically, the adoption of EOQ enables the company to reduce inventory costs by up to 12% annually. Additionally, inventory turnover rates increase to 14.59 times for wheat flour and 12.29 times for granulated sugar. These results demonstrate that the EOQ method is a more effective tool for supporting efficient inventory management within the company’s operational context